2022
DOI: 10.1093/hsw/hlac003
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Stressors of Parents of Trans and Gender-Diverse Youth in Clinical Care from Trans Youth CAN!

Abstract: Parents of trans and gender-diverse youth can experience challenges navigating gender-affirming (GA) care such as stigma, transphobia, and lack of support. There is little information available about stressors, worries, and positive feelings of parents as they try to support their youth accessing GA care. This article presents baseline survey data on experiences and stressors of 160 parents/caregivers in the Trans Youth CAN! cohort study, which examined medical, social, and family outcomes in youth age 16 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This research study highlighted the different experiences of parents with TNB children living in the studied regions. Similar to parents living in large urban centres, these parents frequently report experiences of grief, anxiety, and vulnerabilities [12,17,29,46,[55][56][57][58][59]. These findings, both on an individual and family level, are similar to those living in regional or urban areas.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…This research study highlighted the different experiences of parents with TNB children living in the studied regions. Similar to parents living in large urban centres, these parents frequently report experiences of grief, anxiety, and vulnerabilities [12,17,29,46,[55][56][57][58][59]. These findings, both on an individual and family level, are similar to those living in regional or urban areas.…”
Section: Discussionmentioning
confidence: 69%
“…Because TNB youth are more likely to experience adversity than cisgender youth (i.e., those whose gender corresponds to the sex assigned at birth), parents of TNB children often have many concerns, such as their child being rejected, experiencing violence or transphobia, or self-harming [17]. Various studies have also shown that parental support is a key factor in the well-being of young TNB, reducing the risk of suicide, anxiety disorders, and other mental health problems [12,[18][19][20][21][22][23][24][25].…”
Section: Experience Of Parents Of Tnb Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research is demonstrating the importance of providing gender-affirming health care (Salas-Humara et al, 2019), which is linked to improved emotional wellbeing, decreased suicidal ideation and deaths by suicide, and improved quality of life (Allen et al, 2019; Turban et al, 2020). Parent acceptance and support is critical to the wellbeing of these youth, as is support for the parents themselves who report difficulty helping their children navigate health systems, tension in interpersonal relationships, concern about their child’s well-being, and stress as they make medical decisions (Sansfaçon et al, 2022). Buckloh et al’s (2022) article outlining best practices in working with parents of gender diverse provides a robust overview of issues commonly navigated as part of care and offer concretes guidance for how to facilitate parent–child communication, collaborate with the medical team, and provide interventions to parents as they journey alongside their children.…”
Section: Diversity Equity Access and Inclusion Considerations In Pare...mentioning
confidence: 99%